Clinical manual of adolescent substance abuse treatment - Ḳaminer, Yifraḥ 1951-.; Winters, Kenneth C.; IG Publishing (Washington, DC American Psychiatric Pub., 2011)
Clinical Manual of Adolescent Substance Abuse Treatment brings together extensive new research in the field of adolescent substance abuse to serve as a comprehensive resource for psychiatrists, psychologists, social workers, substance abuse specialists, and other clinicians, as well as residents and students of psychology.
Diagnosis, epidemiology, and course of youth substance use and use disorders / Tammy Chung & Chris Martin -- Prevention of substance use and use disorders: the role of risk and protective factors / Richard Catalano ... [et al.] -- Screening, assessment, and triage for treatment at a primary care setting / Sharon Levy, John Knight & Ken Winters -- Bio-essays and the detection of substances of abuse in youth: challenges and opportunities / Janelle Arias, Albert Arias & Yifrah Kaminer -- Placement criteria and integrated treatment services for adolescents with psychiatric comorbidity / Marc Fishman -- From assessment through treatment (in)to aftercare: continuity of care and outcome / Ken Winters & Yifrah Kaminer -- Pharmacotherapy of adolescent substance use disorders / Yifrah Kaminer & Lisa Marsch -- Club drugs, prescription, and over the counter medication abuse: description, diagnosis, and intervention / Christian Hopfer -- Brief motivational interventions and contingency management for youth substance use disorders / Yifrah Kaminer, Anthony Spirito & William Lewander -- Family therapies and community reinforcement approach for youth substance use disorders / Gayle Dakof, Susan Godley & Jane Ellen Smith -- Twelve-step mutual help programs for youth substance use disorders / Steve Jaffee & John Kelly -- Assessment and treatment of comorbid attention deficit-disruptive disorders / K.A.H.Mirza & Oscar Bukstein -- Assessment and treatment of comorbid internalizing disorders (depression, anxiety disorders, and PTSD) / Yifrah Kaminer, Julian Ford & Duncan Clark -- Assessment and treatment of comorbid suicidal behavior / David Goldston ... [et al.] -- Assessment and treatment of comorbid psychotic disorders (bi-polar, schizophrenia, and drug induced) / Robert Milin, Selena Walker & Anne Duffy -- Management of youth with substance use disorders in the juvenile justice system / Peter Rockholz.
Electronic reproduction.
Keywords: Teenagers -- Substance use; Substance abuse -- Treatment; Electronic books